Cut flowers and foliages - Faust, James E. (Associate Professor); Dole, John M. (John Martin) (Crop production science in horticulture ;, 2021)
"The cut flower industry is a global business with major production locations around the world. This book describes the major international production locations and markets, including current trends and directions"--